THE EVOLUTION OF CONTENT MARKETING: FROM TRADITIONAL ADVERTISING TO STORYTELLING AND BRAND NARRATIVES - Jurakulov Asror Abrorovich (Web of Journals Publishing, 2023)
Content marketing has witnessed a transformative journey from conventional advertising strategies to the contemporary approach of storytelling and brand narratives. This evolution has been driven by changing consumer preferences and advancements in communication channels. This article explores the historical shift in content marketing, analyzing the factors contributing to the rise of storytelling and brand narratives. By employing a qualitative research methodology, including literature review and case studies, the article delves into the effectiveness and engagement levels of these modern strategies compared to traditional advertising. The findings highlight the significant impact of emotionally resonant content in fostering stronger connections between brands and consumers in today's dynamic digital landscape.
Keywords: Content marketing, traditional advertising, storytelling, brand narratives, consumer engagement.